Pengaruh Model Discovery Learning Berbantuan Multimedia Interaktif terhadap Kemampuan Berpikir Tingkat Tinggi pada Materi Pubertas Kelas VI SD - Miftahus Silmi Zohro; Endang Widi Winarni; Irwan Koto (UNIB Press, 2024)
This study aims to examine the influence of the Discovery Learning (DL) model assisted by Interactive Multimedia on students' higher-order thinking skills in the topic of Puberty for sixth-grade students. This research is quantitative in nature, which means it utilizes numerical data collection and analyzes it using statistics, data interpretation, and presentation of research findings to determine the relationship between two variables. The results of the study indicate a significant improvement in students' higher-order thinking skills when using the DL model assisted by media. Hypothesis testing shows a significant difference between pretest and posttest scores in both groups, with an increase of approximately 46% in the moderate category for the ability to identify problems. The mean scores of students' pretest and posttest higher-order thinking skills increased from 53.35 to 74.95. Although there was an improvement, students' higher-order thinking skills still fall into the moderate category. This study concludes that the implementation of the DL model assisted by media has a significant impact on students' higher-order thinking skills; however, more practice and experimentation are needed to enhance these abilities.